Reduction of inappropriate perioperative neurology outpatient referrals for perioperative risk assessment and antithrombotic risk management in a major academic hospital - Deidre Anne De Silva; Yingke He; Bridget Ng Si Min; Yu Zhi Pang; Eunice Kok Jie Yi; Zhao Han Goh; Fernandina Setiawan; Ignasius Jappar; Hairil Rizal Bin Abdullah (BMJ Open Quality)
Perioperative stroke, a rare but serious complication, refers to any thrombotic, embolic or haemorrhagic cerebrovascular event lasting more than 24 hours, occurring intraoperatively or within 30 days of surgery. Preoperative assessment is critical for identifying high-risk patients and mitigating stroke risks. Despite established guidelines, a lack of standardised protocols at our institution led to inappropriate neurology referrals and unnecessary suspension of antithrombotics. At our preoperative evaluation clinic, which assesses 100–120 patients daily, challenges arose in managing patients at risk of perioperative stroke. An analysis from April to September 2022 revealed that 83.3% of 24 neurology referrals were inappropriate, causing surgical delays due to medicolegal concerns, surgery postponement fears and unclear guidelines. To address this, a quality improvement project was launched to reduce inappropriate neurology referrals by 15% in 6 months. The secondary aim was to create standardised management guidelines and evaluate both the incidence of surgical postponements and perioperative stroke outcomes.The project employed the plan–do–study–act framework, with interventions including the development of easily accessible standardised protocols and staff education through roadshow education platforms. Postintervention analysis showed a statistically significant 16.6% reduction in inappropriate neurology referrals (p=0.04), surpassing the 15% reduction target. Surgical postponements due to preoperative neurology consultations also decreased. There were no perioperative strokes reported during the project period, ensuring that the patient safety was not compromised. Additionally, the intervention resulted in cost savings of approximately $2134 annually by avoiding unnecessary consultations.This project highlights the effectiveness of multidisciplinary collaboration in reducing inappropriate neurology referrals and improving perioperative stroke risk management. The standardised guidelines have streamlined workflows and enhanced patient care, with sustained efforts planned to ensure long-term adherence to these protocols. Future directions include expanding the implementation of standardised protocols to other specialties within the institution.